Russia’s War in Ukraine as a “War for Identity” and Appropriation of Cultural Tradition - Mishalova, Olena; Hordiichuk, Olha; Sokolovskyi, Oleh (Wydział Filozoficzny UAM, 2024)
The article analyzes Russia’s current war in Ukraine through the perspective of Francis Fukuyama’s concept of identity politics based on Samuel Huntington’s civilization approach. We argue that Russia’s war against Ukraine is a new type of war – a “war for identity” – a war that is waged primarily for the appropriation of Ukrainian cultural identity and historical heritage, rather than for political or economic resources. We believe that an effective explanatory framework for its consideration is provided by Huntington’s civilizational concept of the world order, in which the most widespread and dangerous conflicts will be between peoples belonging to different civilizations (and cultures). The article emphasizes that the Russian war in Ukraine is a direct consequence of two factors: on the one hand, Russia is not satisfied with its own cultural tradition and seeks to appropriate Ukrainian cultural identity and historical heritage in order to restore the “lost empire”; on the other hand, Russia is historically a region of civilizational fault line between the countries of Western civilization and the countries of Eastern civilizations, it is a “torn” state in terms of cultural identity and has maintained its integrity for centuries only due to its authoritarian political regime, but constantly produces numerous conflicts around its borders.
Keywords: Cultural identity; civilization; cultural heritage; Ukraine; war for identity; failed state; Russia